1995
DOI: 10.1073/pnas.92.10.4656
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between quantitative trait loci in soybean in which trait variation at one locus is conditional upon a specific allele at another.

Abstract: A large recombinant inbred population of soybean has been characterized for 220 restriction fragmentlength polymorphism (RFLP) unlinked locus (which, by itself, is not associated with trait variation). This type of interaction is shown schematically in Fig. 1. In this example, a difference in height produced by different alleles at locus 1 is conditional upon the presence of a Noir 1 allele at locus 2. Only the RI lines with the Noir 1 allele at locus 2 will show differences in height produced by the first l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
125
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(138 citation statements)
references
References 2 publications
8
125
0
5
Order By: Relevance
“…The d 2 g , which cannot be explained by detected QTL, may be attributed to QTL with smaller effects, and/or due to QTL 3 QTL interactions referred to as epistatic interaction. Epistasis is the phenotypic effect of interaction among alleles at multiple loci (Xing et al, 2002) that play an important role in the genetic basis of quantitative traits (Lark et al, 1995;Li et al, 1997;Yu et al, 1997). We understand that the distances between marker loci and the QTL biased the estimated effects of epistasis.…”
Section: Qtl 3 Qtl Interactionsmentioning
confidence: 99%
“…The d 2 g , which cannot be explained by detected QTL, may be attributed to QTL with smaller effects, and/or due to QTL 3 QTL interactions referred to as epistatic interaction. Epistasis is the phenotypic effect of interaction among alleles at multiple loci (Xing et al, 2002) that play an important role in the genetic basis of quantitative traits (Lark et al, 1995;Li et al, 1997;Yu et al, 1997). We understand that the distances between marker loci and the QTL biased the estimated effects of epistasis.…”
Section: Qtl 3 Qtl Interactionsmentioning
confidence: 99%
“…The interaction between genes is an important source of genetic variability and its effects are larger than the quantitative theory implied (Moreno 1994). In studying pairs of quantitative trait loci (QTL) in soybean, Lark et al (1995) reported that interactions between QTL are frequent and control large effects. They also found that an allele at one locus with little or no variation by itself exerted a large effect on height via interaction with other loci.…”
Section: Introductionmentioning
confidence: 99%
“…Strong interactions between QTLs have also been observed in maize (Lukens and Doebley 1999) and soybean (Lark et al 1995). Recent genetic analyses using molecular markers in several plant species have clearly shown that, in addition to single locus QTLs, epistatic interactions play an important role on the genetic basis of quantitative traits (Lark et al 1995;Maughan et al 1996;Li et al 1997;Yu et al 1997;Poelwijk et al 2011;Krajewski et al 2012;Bocianowski 2012cBocianowski , 2013Bocianowski , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Epistasis or the additive-by-additive interaction between loci on a genome that controls a quantitative trait is of great interest to geneticists (Eta-Ndu and Openshaw 1999; Gao and Zhu 2007;Kang et al 2009;Zuo and Kang 2010;Binh et al 2011;He et al 2011). Strong interactions between QTLs have also been observed in maize (Lukens and Doebley 1999) and soybean (Lark et al 1995). Recent genetic analyses using molecular markers in several plant species have clearly shown that, in addition to single locus QTLs, epistatic interactions play an important role on the genetic basis of quantitative traits (Lark et al 1995;Maughan et al 1996;Li et al 1997;Yu et al 1997;Poelwijk et al 2011;Krajewski et al 2012;Bocianowski 2012cBocianowski , 2013Bocianowski , 2014.…”
Section: Introductionmentioning
confidence: 99%